Changing epidemiology of bloodstream infections associated with central venous catheters in patients after stem cell transplantation: increasing frequency of identification of Gram-negative pathogens - Raddaoui, Anis; Mezzi, Khaoula; Belloumi, Dorra; Frigui, Siwar; Ben Othmen, Tarek; Abdejlil, Nour; Chebbi, Yosra; Achour, Wafa (Journal of Medical Science, 2026)
Introduction. The frequent use of central venous catheters (CVC) in haematopoietic stem cell (HSC) transplant patients exposes them to a high risk of catheter-related bloodstream infections (CRBSI). The aim of this study was to estimate the prevalence of CRBSI in HSC transplant patients and to describe their clinical and bacteriological characteristics.Material and methods. A retrospective study (January 2011-December 2022) including 60 episodes of CRBSI occurring in the pre- or post-HSC transplant period in 56 patients was conducted in the Haematology and Transplant Department of the National Bone Marrow Transplant Centre. Results. The prevalence of CRBSI was 4.9%. The median time between CVC placement and CRBSI was nine days. Gram-negative bacilli (GNB) CRBSI (N=33, 55%) were more frequent than gram-positive cocci (GPC) CRBSI (N=27, 45), with a GNB/GPC ratio of less than one before 2019, rising to two between 2019 and 2022. First-line antibiotic therapy was based mainly on Piperacillin-tazobactam (60%). Removal of the CVC was indicated in 51% of cases. Mortality associated with CRBSI was 0.32% (4/1217). Conclusion. The increase in CRBSI prevalence and the high rate of antibiotic resistance highlight the need for heightened awareness, ongoing training for healthcare staff, and judicious antibiotic use.
Keywords: bloodstream infection; central venous catheter; transplant-hematopoietic stem cell; antibiotic resistance